Tribology in Sheet Rolling Technology - Azushima, Akira (Springer International Publishing : Imprint: Springer, 2016)
This book provides an in-depth description of the fundamental tribological aspects of cold and hot sheet rollings. The author describes new developments in the rolling processes, the rolling oils, the rolling rolls and the structural materials resulting from sheet rolling technology and their practical applications. The author includes comprehensive details on both friction and lubrication in rolling.